MEDIASI KEPUASAN KERJA PADA HUBUNGAN ANTARA STRES KERJA DAN KEPUASAN HIDUP KARYAWAN PERUSAHAAN PERMINYAKAN - Widjajani, Susi; Handayani, Pika (Optimum: Jurnal Ekonomi dan Pembangunan, 2013)
This study to determine (1) whether the job stress has a significant influence on life satisfaction (2) whether the job stress has a significant influence on job satisfaction (3) whether the job satisfaction has a significant influence on life satisfaction and (4) whether the job satisfaction mediates the relationship between job stress and life satisfaction.The object of this study is PT. Chevron Pacific Indonesia, located in Riau Rumbai. In this study, the population are employees office at PT. Chevron Pacific Indonesia, Riau Rumbai. Kinds of data which werw collected, consist of primary data and secondary data. This study uses purposive sampling techniques with 204 respondents. Data analysis was done by using path Analysis with the help of software, SPSS 18.0, for windows. The results obtained are as follows: There is no relation between job stress on life satisfaction, between job stress and job satisfaction, and indirect relation on job stress and life satisfaction through the mediation of job satisfaction.